Core attributes of interactive computer games and adaptive use for edutainment - Khine, Myint Swe; Shalleh Bin Suja'Ee, M. (2008)
Playing computer games is a routine activity of children today. They play different genres of games in different settings and on varying platforms. In recent years educators beginning to take interest in this phenomena and explore the characteristics of the computer games that allure children of all ages. Many have agreed that interactive computer games enhance concentration, promote critical thinking, increase motivation and encourage socialisation. This paper examines the core attributes of some of the interactive computer games and suggests how these attributes can be adapted in the lessons as edutainment that can captivate and delight the students in day-to-day teaching in the classrooms. © 2008 Springer-Verlag Berlin Heidelberg.